Isolation and Identification of Phenolic Compounds from Ebony Plant Leaves (Diospyros celebica Bakh.) - Purba, Yuni Romasni; Sembiring, Helmina Br. (Talenta Publisher, 2022)
Isolation of phenolic compounds from Ebony plant leaves (Diospyros celebica Bakh .) was done by maceration technique with methanol solvent. The concentrated extract of methanol dissolved with distilled water and partition was extracted with ethyl acetate. The concentrated ethyl acetate extract dissolved with methanol solvent and partitioned with n-hexane. Then Thin layer chromatography was analyzed before column chromatography, and the eluent suitable for separation is chloroform: methanol 90:10, 80:20, 70:30,60:40,50:50 (v/v) as mobile phase. The compounds were purified with a thin layer preparative and crystallization yielding yellow paste weighing 7.5 mg with Rf = 0.45. The test purity of compounds is done by thin layerÂ chromatography showing a single spot with eluent chloroform: ethyl acetate (50:50) v/v and n-hexane: ethyl acetate ( 80:20) v/v. The following compound was further indicated by Ultraviolet-Visible Spectrophotometer (UV-Vis), Fourier Transform Infra Red Spectrophotometer (FT-IR), and Proton Nuclear Magnetic Resonancy Spectrophotometer (1H-NMR) was estimated as a phenolic methyl gallate, phenolic acid.